Role of short-chain fatty acids in non-alcoholic fatty liver disease and potential therapeutic targets - Xiang Qin; Mengyao Chen; Beihui He; Beihui He; Yuyan Chen; Yuelin Zheng (Frontiers in Microbiology)
Non-alcoholic fatty liver disease (NAFLD) is increasing worldwide and has become the greatest potential risk for cirrhosis and hepatocellular carcinoma. The metabolites produced by the gut microbiota act as signal molecules that mediate the interaction between microorganisms and the host and have biphasic effects on human health. The gut microbiota and its metabolites, short-chain fatty acids (SCFAs), have been discovered to ameliorate many prevalent liver diseases, including NAFLD. Currently, SCFAs have attracted widespread attention as potential therapeutic targets for NAFLD, but the mechanism of action has not been fully elucidated. This article summarizes the mechanisms of short-chain fatty acids of gut microbiota metabolites to regulate the metabolism of glucose and lipid, maintain the intestinal barrier, alleviate the inflammatory response, and improve the oxidative stress to improve NAFLD, in order to provide a reference for clinical application.